2020
DOI: 10.1073/pnas.1918088117
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of the K ATP channel Kir6.2 subunit promotes channel opening by regulating PIP 2 sensitivity

Abstract: A physiological role for long-chain acyl-CoA esters to activate ATP-sensitive K+ (KATP) channels is well established. Circulating palmitate is transported into cells and converted to palmitoyl-CoA, which is a substrate for palmitoylation. We found that palmitoyl-CoA, but not palmitic acid, activated the channel when applied acutely. We have altered the palmitoylation state by preincubating cells with micromolar concentrations of palmitic acid or by inhibiting protein thioesterases. With acyl-biotin exchange as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Similar experiments performed in rat cardiomyocytes confirmed the S-acylation of Kir6.2 and showed that this modification was enhanced following incubation of the cells with either palmitate or a combination of ML348 and ML349, selective inhibitors of the thioesterases APT1 and APT2, respectively [ 31 ]. Electrophysiological recordings of inside-out membrane patches showed that treatment with palmitate or ML348/ML349 promoted an increase in mean patch current and open time and decreased sensitivity to ATP; these effects were seen for endogenous channels in rat cardiomyocytes and INS1 pancreatic β-cells, and in HEK293 cells transfected with Kir6.2 together with SUR1 or SUR2A [ 31 ]. Assuming that the effect of these treatments reflects changes in the S-acylation of Kir6.2, it is likely that S-acylation regulates the gating or the modulation of K ATP activity as cell surface levels of the channel were unaffected [ 31 ] ( figure 2 ).…”
Section: Insulin Secretionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similar experiments performed in rat cardiomyocytes confirmed the S-acylation of Kir6.2 and showed that this modification was enhanced following incubation of the cells with either palmitate or a combination of ML348 and ML349, selective inhibitors of the thioesterases APT1 and APT2, respectively [ 31 ]. Electrophysiological recordings of inside-out membrane patches showed that treatment with palmitate or ML348/ML349 promoted an increase in mean patch current and open time and decreased sensitivity to ATP; these effects were seen for endogenous channels in rat cardiomyocytes and INS1 pancreatic β-cells, and in HEK293 cells transfected with Kir6.2 together with SUR1 or SUR2A [ 31 ]. Assuming that the effect of these treatments reflects changes in the S-acylation of Kir6.2, it is likely that S-acylation regulates the gating or the modulation of K ATP activity as cell surface levels of the channel were unaffected [ 31 ] ( figure 2 ).…”
Section: Insulin Secretionmentioning
confidence: 75%
“…Functional K ATP channels consists of four Kir6.x subunits, which assemble together with 4 SUR subunits, and in pancreatic β-cells these channels are composed of Kir6.2 and SUR1 subunits. A recent study using ABE assays on co-transfected HEK293 cells suggested that Kir6.2 (but not SUR1) is modified by S-acylation [ 31 ]. Similar experiments performed in rat cardiomyocytes confirmed the S-acylation of Kir6.2 and showed that this modification was enhanced following incubation of the cells with either palmitate or a combination of ML348 and ML349, selective inhibitors of the thioesterases APT1 and APT2, respectively [ 31 ].…”
Section: Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP binding to one of four ATP binding sites has already been reported to close the channel [ 136 ]. Moreover, the palmitoylation of Cys166 of Kir6.2 was found to enhance its sensitivity to PIP 2 [ 137 ].…”
Section: Revisited Mechanism Of Glucose-stimulated Insulin Secretimentioning
confidence: 99%
“…Phosphatidylinositol 4,5‐bisphosphate (PIP2) can activate membrane protein channels (i.e., inward‐rectifying potassium channels) [ 105 ] by direct binding but the membrane environment or allosteric presence of other lipids also contributes to channel activity. [ 106 ] The inward rectifier K + channel Kir6.2 becomes sensitized to PIP2 when palmitoylated but an additional lipid acyl chain also contributes hydrophobic contacts to the PI binding site, [ 107 ] and the closely related Kir2.2 exhibits allosteric binding by PS at an additional, anionic lipid binding site. [ 106 ] PIP2 itself can act by different modes on different membrane proteins.…”
Section: Interactions Between Membrane Proteins and Lipids Are Finely Tunedmentioning
confidence: 99%